Connectivity and complexity of floodplain habitats govern zooplankton dynamics in a large temperate river system. (3rd May 2013) - Górski, Konrad; Collier, Kevin J.; Duggan, Ian C.; Taylor, Claire M.; Hamilton, David P.
Summary Large river–floodplain systems are characterised by seasonal flow variability. High flows lead to hydrological connection between the main channel and inundated off‐channel lakes, wetlands and floodplains, which provide essential habitats for riverine biota. We tested the following hypotheses: (i) that crustacean zooplankton are more abundant in connected lentic habitats such as riverine lakes and wetlands and have a different community composition compared with the main channel and (ii) that vegetation structure will moderate abundances of crustacean zooplankton in the lower reaches of the Waikato River, New Zealand. Zooplankton densities in main channel inflows and inundated floodplains showed clear seasonal changes, with cladoceran and copepod abundance peaks occurring in the majority of sites 2–3 weeks following the peak spring discharges (coinciding with the retreat of water from floodplains into the main channel). Mean densities of zooplankton were highest in the inflows originating from riverine lakes (10–20 ind. L−1) where rotifers were dominant. We recorded significantly higher abundances of copepods in peat bog and swamp wetland inflows (c. 5 ind. L−1) relative to the main river channel and riverine lake inflows (0.1–1 ind. L−1). Some lake inflows also had high numbers of cladocerans (5–10 ind. L−1). Inundated floodplains displayed heterogeneity in zooplankton community composition in relation to their structural complexity. Flooded forest accommodated higher numbers of copepods (c. 8 ind. L−1) and cladocerans (c. 17 ind. L−1) than flooded grassland, where zooplankton assemblages resembled those in the main river channel and were characterised by dominance of rotifers and low overall zooplankton densities (1–2 ind. L−1). Our results suggest that seasonal flow and flood pulses, which determine the degree of connectivity of the main channel with the floodplain and off‐channel habitats, govern zooplankton densities and community structure in this large temperate river. Furthermore, the structural complexity of floodplain habitats may play an important role in enhancing riverine zooplankton diversity. We postulate that the post‐flood peak of large‐bodied cladocerans and copepods might have historically played an important role in the provision of food for juvenile fish such as migrating Galaxiidae.